2021
DOI: 10.1061/(asce)cf.1943-5509.0001624
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Building System Manufacturer Selection Decision Framework for Integration into Total Cost of Ownership Evaluations

Abstract: Facility managers are often faced with building system procurement or replacement decisions, requiring them to select a system from among competitive manufacturers. Total cost of ownership (TCO) criteria, informed by built assets in operation in the manager's portfolio, provides some information to select the right asset manufacturer. However, managers must also consider technical performance to complete a more comprehensive analysis. Performance can be calculated using asset parameters like condition, age, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Manufacturer C only produces air handlers. This naming convention is consistent with that which is proposed in previous work that provides additional detail (Brown et al 2021). This analysis does not aim to provide definitive conclusions about which manufacturer, by name, an organization should procure.…”
Section: Data and Case Studysupporting
confidence: 88%
See 4 more Smart Citations
“…Manufacturer C only produces air handlers. This naming convention is consistent with that which is proposed in previous work that provides additional detail (Brown et al 2021). This analysis does not aim to provide definitive conclusions about which manufacturer, by name, an organization should procure.…”
Section: Data and Case Studysupporting
confidence: 88%
“…A case study using observed, manufacturer-level infrastructure data was conducted to investigate the link between built infrastructure asset performance and climate. This case study builds upon the work of Brown et al (2021) in the development of a performance-based metric to quantify the performance of assets and link relevant climate data to investigate any trends that may exist. This analysis used built infrastructure asset data from BUILDER TM Sustainment Management System, an industryleading program used to track and manage infrastructure assets (BUILDER Sustainment Management System 2012).…”
Section: Data and Case Studymentioning
confidence: 99%
See 3 more Smart Citations